Pengaruh Tingkat Penghasilan, Sanksi Pajak, dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus Pada KPP Pratama Gresik) - Febriyanti, Sintya Ayu; Sari, Arista Fauzi Kartika; Hariri, Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of income levels, tax sanctions and tax knowledge on individual taxpayer compliance (a case study at KPP Pratama Gresik). The independent variables in this study are the level of income, tax sanctions and knowledge of taxation while the dependent variable is individual taxpayer compliance. This type of research is quantitative research, because the data used is in the form of numbers and numbers. Source of data in this study is primary data with data collection methods in the form of questionnaires. The population in this study are individual taxpayers who are registered at KPP Pratama Gresik. The data collection technique uses the slovin formula. Based on this method, the number of individual taxpayers used is 100 respondents. The hypothesis was tested using descriptive statistical analysis, instrument testing, normality test, classical assumption test, multiple linear regression analysis test, and hypothesis testing using SPSS Version 25. The results showed that the income level variable had no effect on individual taxpayer compliance (0.567 > 0 .05), the tax penalty variable has a positive and significant effect on taxpayer compliance (0.007 <0.05), and the tax knowledge variable has a positive and significant effect on taxpayer compliance (0.033 <0.05).Keywords: Income level, tax sanctions, tax knowledge and individual taxpayer compliance